Organelle genome complexity scales positively with organism size in volvocine green algae - Smith, David R.; Hamaji, Takashi; Olson, Bradley J.; Durand, Pierre M.; Ferris, Patrick; Michod, Richard E.; Featherston, Jonathan; Nozaki, Hisayoshi; Keeling, Patrick J. (My University, 2013)
It has been argued that for certain lineages noncoding DNA expansion is a consequence of the increased random genetic drift associated with long-term escalations in organism size. But a lack of data has prevented the investigation of this hypothesis in most plastid-bearing protists. Here, using newly sequenced mitochondrial and plastid genomes, we explore the relationship between organelle DNA noncoding content and organism size within volvocine green algae. By looking at unicellular, colonial, and differentiated multicellular algae, we show that organelle DNA complexity scales positively with species size and cell number across the volvocine lineage. Moreover, silent-site genetic diversity data suggest that the volvocine species with the largest cell numbers and most bloated organelle genomes have the smallest effective population sizes. Together, these findings support the view that non-adaptive processes, like random genetic drift, promote the expansion of noncoding regions in organelle genomes.
Keywords: Chlamydomonas; Gonium; Pleodorina; Volvox; Mitochondrion; Chloroplast